(untitled) (Asian Journal of Medical Research and Health Sciences, 2026)
Background: Chronic hair fall with non-scarring alopecia is a significant psychological burden, making the response to monotherapy slow and incomplete. Using PRP together with topical minoxidil could be more effective at enhancing hair density as they work in synergy. Methods: This prospective observation study assessed the safety and efficacy of PRP and topical minoxidil combination therapy in chronic hair fall patients. 72 patients with androgenetic alopecia or chronic telogen effluvium for over six months were injected monthly with a platelet-rich plasma for four months and applied with a topical minoxidil for six months. Clinical assessment, standardised global photography, hair-pull test, trichoscopic evaluation of hair density, mean hair shaft diameter, Dermatology Life Quality Index and adverse events were recorded at baseline, 3 and 6 months. Results: Mean hair density increased from 91.6 +/- 18.8 hairs/cm2 at baseline to 113.4 +/- 20.7 hairs/cm2 at three months and 129.8 +/- 23.1 hairs/cm2 at six months (p<0.001). Hair-pull positivity decreased from 65.3% to 15.3% (p<0.001), and mean DLQI improved from 9.2 +/- 3.4 to 4.1 +/- 2.2 (p<0.001). Of the patients, 52.8% showed good or excellent improvement globally at 6 months. Conclusion: The adverse events were mild, and consisted of transient injection-site pain, erythema at the injection site, headache and irritation associated with minoxidil. PRP + minoxidil therapy was found to be safe and effective for chronic hair fall with marked clinical and trichoscopic improvement.